MENENTUKAN KEBUTUHAN NITROGEN, FOSFOR DAN KALIUM UNTUK TANAMAN JAGUNG BERDASARKAN TARGET HASIL DAN EFISIENSI AGRONOMIK PADA LAHAN KERING ULTISOL LAMPUNG - Anadarias Makka Murni (Jurnal Ilmu Tanah dan Lingkungan, 2008)
To obtain the rational fertilizer recommendation for maize in Lampung, the experiment had been conducted in three continuous years. The aims of the experiment were to determine nitrogen (N), phosphorus (P) and potassium (K) requirements for maize based on yield target. The experiments were conducted in Tegineneng, South Lampung during the rainy season of 2005, 2006 and 2007. The experiments were designed in omission plot and NPK treatments namely 1) 0 kg N +35 kg P + 100 kg K ha-1 (N0P35K100), 2) 200 kg N + 0 kg P + 100 kg K ha-1 (N200P0K100) 3) 200 kg N + 35 kg P + 0 kg K ha-1 (N200P35K0) and 4) 200 kg N + 35 kg P + 100 kg K ha-1 (N200P35K100). Randomized block design with 5 replications was used in the experiments. The results showed that the omitted N > K > P significantly reduced the yield of maize. Yield responses to fertilizer were N = 2.6-4.1, P = 0.57-2.0 and K = 1.6-2.4 t ha-1 and agronomic efficiencies of nutrients were N = 13-21, P = 19-57 and K = 16-24 kg yield kg-1 nutrient. Thus, based on the yield target agronomic efficiencies, the N, P and K requirement for maize at Lampung Ultisol are N = 125-200, P2O5 = 25-100, and K2O = 30-120 kg ha-1 with the yield target of 7-10 t ha-1.Keywords: Omission plot, NPK requirement,Ultisol, zea mays, Lampung